Islam, HAM, dan Diskriminasi: Reinterpretasi Hadis-Hadis Kepemimpinan secara Kontekstual - Muhammad Syachrofi (El-Afkar: Jurnal Pemikiran Keislaman dan Tafsir Hadis, 2021)
This paper discusses one of the humanitarian problems that still often occurs today, discrimination. Discrimination is not only contrary to human rights but also contrary to the Islamic view which is raḥmah fī al-‘ālamīn. But, in fact, Islam is always suspected as a religion that teaches various forms of discriminatory treatment. The accusation is based on Islamic religious texts which narratively teach discrimination. I find that there are two hadiths that are discriminatory about electing leaders. The first hadith is about having to elect a leader from the Quraysh clan. The second hadith is about the prohibition for women to be a leader. Textually, these hadiths are quite problematic because they contain the narration of racial-ethnic discrimination and gender discrimination. Therefore, in this article, I attempt to reinterpret these hadiths by using a contextual approach by analyzing the language and socio-historical context. My conclusion is that these hadiths were stated by the Prophet Muhammad in temporary cases. Substantially, these hadiths contain the significances that are relevant today.